National Competitiveness of Kenya and its oil cluster - Busiyile, Brian Simiyu (Strathmore University, 2009)
Oil is critical to western type civilization. The United States of America (USA), the icon of this civilization, uses up 24% of the world’s oil per day. Oil is critical for the global economy. Similarly, oil is the fulcrum of Kenya’s economy. Even though Kenya uses only 0.08% of the world’s oil per day, yet this small proportion drives investment, influences consumption and sets the pace of economic growth. Transport, power generation, manufacturing and agricultural sectors are dependent of the supply and affordability of petroleum products. Currently, about 22% of Kenya’s primary energy is drawn from oil. For this reason, it can be argued that the competitiveness of the Kenyan economy is directly linked to competitiveness of the oil industry. As Kenya embarks on the Vision 2030, any action that improves its competitiveness will accelerate the realization of this vision. In this dissertation, the ‘Theory of Competitive Advantage of Nations’ by Michael Porter, commonly referred to as the diamond model, has been applied to analyze the competitiveness of Kenya and its oil industry in order to identify challenges and opportunities and to recommend actions that stakeholders can and should take to enhance their competitiveness. Based on the diamond model and related variables adapted from the Global Competitiveness Report and Index data, an assessment of the competitiveness of Kenya and its oil cluster was undertaken. This dissertation first sought to identify the challenges and opportunities for Kenya and then it proposed the way forward to stakeholders on how to make Kenya more competitive at national, regional and international levels. The methodology employed in this cross-sectional study, was essentially descriptive and comparative. Kenya’s scores and rankings in the Global Competitiveness Report and the World Bank doing business report were compared with other countries in East Africa region and the leading ones to arrive at the study findings. The study used secondary data exclusively. Since the diamond elements are not directly measured, this dissertation proposed and used some proxy factors to indicate the scores on the diamond as follows. These are :- 1. Factors conditions comprising of the pillars on infrastructure, Health and Primary Education and the Labour market efficiency 2. Demand conditions comprising of the Gross Domestic Product (GDP), pillars on Higher Education and Training , technological readiness and market size. 3. Related and supporting industry comprising pillars on Financial Market sophistication and business sophistication ; and 4. Context of Firm Strategy, Structure and Rivalry comprising pillars on Market efficiency and Innovation Following the analysis, twelve challenges and five opportunities were identified and a national agenda proposed to boost competitiveness. From the study, Kenya was deemed competitive regionally but not internationally. Further, the study shows that the Kenya private sector is competitively ranked regionally, but that the public sector is unfavourably ranked. Even though competitiveness can only be fully realized in synergy and cooperation between public and private sector players, yet it can be argued that in Kenya’s case, the step-change in gain towards competitiveness lies first and foremost in comprehensive public sector reforms then an acceleration of public and private sector cooperation. The governments’ Vision 2030 recognizes this fact and implementation is already ongoing. In driving competitiveness Kenya must seek to work with other neighbouring countries to tap into joint regional advantages such as the growing economies, large market potential and the continuing oil exploration and production efforts, which have yielded oil and gas finds. Kenya on her part, has intensified her oil exploration programme but should similarly dedicate more resources to research and development of alternative fuels technology notably bio-fuels that would easily be blended with fossil fuels. This would reduce dependence on foreign oil and reduce the shock on the Kenyan economy whenever there are wild swings in global prices of crude oil. The main study limitations were identified and future areas of research to build on it were proposed. The details of the research are discussed in this report.
Partial fulfillment for award of Master of Business Administration
Keywords: Kenya -- Oil Cluster; Diamond Model Analysis; Competitiveness